Efecto de la temperatura de carburización utilizando medio difusor: 80% viruta de fundición gris y 20% baco3, sobre la resistencia a la tracción, ductilidad, resistencia al impacto, espesor de capa, dureza superficial y dureza en el núcleo en el acero aisi 3215 - Alarcon Arce, William (2016)
We have studied the effect of temperature carburization in the steel AISI 3215, using baffle means 80 % chip gray cast iron and 20 % of BaCO3 for a process time of 5 hours at temperatures of 860, 900, 940, 980°C with direct water quenching and tempering at 180°C for 1 hour on tensile strength, ductility, impact resistance, layer thickness, surface hardness and core hardness. Analysis of the experimental results shows that increasing the temperature of carburization in the range of 860 to 980°C, the tensile strength increases from 1032 MPa to 1275 MPa, the ductility decreases from 8.90% to 4.06% and resistance impact also decreases from 28.7 J to 10.3 J. For the layer thickness (X), it increases as the temperature increases from carburization 0.68 mm to 1.45 mm and the results according to the equation x obeys √ . For the surface hardness, it increases as the temperature carburization from 58 HRC to 64.30 HRC increases, this is because the percentage of absorbed carbon on the surface increases slightly with increasing temperature and tempering is obtained martensite high percentage of carbon. And core hardness increased slightly to 940°C and then decreased to 980°C due to the increase of retained austenite. It is concluded that the carburization temperature significantly affects the tensile strength, ductility, impact resistance, layer thickness, surface hardness and core hardness. Also that the diffuser means 80 % chip gray cast iron and 20 % BaCO3 it is efficient because the results correspond to a piece carburized correctly. And statistical analysis with a confidence level of 95 %.